Quality Control of Selected Antimalarials - BABA-MOUSSA, FARID A. KADER SAÏD; DOUGNON, T. VICTORIEN; BONOU, JACOB; BABA-MOUSSA, LAMINE SAÏD (My University, 2015)
Malaria is a parasitic disease caused by the bite of female Anopheles mosquito and particularly affects the tropical areas of the world. According to national statistics it is the leading cause of consultations and hospitalizations. Nowadays, despite the surveillance systems for efficient malaria control and access to generic drugs, Benin is witnessing an increased development of illicit drug markets with a large part of the population going towards such markets. However, this is not without adverse impact on the health of individuals, as well as, the economic status of the country. Therefore, the situation needs to be seriously considered by policy makers at various levels, health professionals but also the entire international community in order to thwart this scourge.Regarding the aforementioned situation, the current study was undertaken aiming to perform a quality control of selected antimalarial drugs of the illegal market in Porto-Novo city. Therefore, 40 antimalarial batches were randomly collected in the illicit drug market and submitted to analytical tests such as: macroscopic examination (a visual and critical examination); mass uniformity test; disintegration test; identification test and active ingredients’ content measurement. At the end of the study, the percentages of non-compliance is 97.5%, 5%, 15% and 27.5%, respectively for the content uniformity tests, disintegration, identification and assay. Over-all, 42.5% of noncompliance was recorded. The findings of this study prove that street vended drugs offer no guarantee of good quality and pose a threat to the health of populations. Also, the rate of non-compliance denotes a flaw in the security of the drug distribution system.
Keywords: Antimalarial; Counterfeit Medicine; Quality Control; Illicit Market